Successful Gastric Volvulus Reduction and Gastropexy Using a Dual Endoscope Technique - Laith H. Jamil; Brian L. Huang; David C. Kunkel; Vijay Jayaraman; Edy E. Soffer (Case Reports in Medicine)
Gastric volvulus is a life threatening condition characterized by an abnormal rotation of the stomach around an axis. Although the first line treatment of this disorder is surgical, we report here a case of gastric volvulus that was endoscopically managed using a novel strategy. An 83-year-old female with a history of pancreatic cancer status postpylorus-preserving Whipple procedure presented with a cecal volvulus requiring right hemicolectomy. Postoperative imaging included a CT scan and upper GI series that showed a gastric volvulus with the antrum located above the diaphragm. An upper endoscopy was advanced through the pylorus into the duodenum and left in this position to keep the stomach under the diaphragm. A second pediatric endoscope was advanced alongside and used to complete percutaneous endoscopic gastrostomy (PEG) placement for anterior gastropexy. The patient’s volvulus resolved and there were no complications. From our review of the literature, the dual endoscopic technique employed here has not been previously described. Patients who are poor surgical candidates or those who do not require emergent surgery can possibly benefit the most from similar minimally invasive endoscopic procedures as described here.